Natural fire regime: a guide for sustainable management of the Canadian boreal forest - Bergeron, Yves; Leduc, Alain; Harvey, Brian; Gauthier, Sylvie (Silva Fennica, 2002)
The combination of certain features of fire disturbance, notably fire frequency, size and severity, may be used to characterize the disturbance regime in any region of the boreal forest. As some consequences of fire resemble the effects of industrial forest harvesting, conventional forest management is often considered as a disturbance that has effects similar to those of natural disturbances. Although the analogy between forest management and fire disturbance in boreal ecosystems has some merit, it is important to recognise that it also has its limitations. Short fire cycles generally described for boreal ecosystems do not appear to be universal; rather, important spatial and temporal variations have been observed in Canada. These variations in the fire cycle have an important influence on forest composition and structure at the landscape and regional levels. Size and severity of fires also show a large range of variability. In regions where the natural matrix of the boreal forest remains relatively intact, maintenance of this natural variability should be targeted by forest managers concerned with biodiversity conservation. Current forest management tends to reduce this variability: for example, fully regulated, even-aged management will tend to truncate the natural forest age distribution and eliminate over-mature and old-growth forests from the landscape. We suggest that the development of strategic-level forest management planning approaches and silvicultural techniques designed to maintain a spectrum of forest compositions and structures at different scales in the landscape is one avenue to maintain this variability. Although we use the boreal forest of Quebec for our examples, it is possible to apply the approach to those portions of the boreal forest where the fire regime favours the development of even-aged stands in burns.